2015
DOI: 10.1002/mc.22358
|View full text |Cite
|
Sign up to set email alerts
|

Mammaglobin 1 promotes breast cancer malignancy and confers sensitivity to anticancer drugs

Abstract: Mammaglobin 1 (MGB1), a member of the secretoglobin family, is expressed in mammary epithelial tissues and is overexpressed in most mammary carcinomas. Despite the extensive research correlating MGB1 expression profiles to breast cancer pathogenesis and disease outcome, the biological significance of MGB1 in cancer processes is still unclear. We have thus set out to conduct a functional evaluation of the molecular and cellular roles of MGB1 in breast cancer processes leading to disease progression. Using a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 54 publications
(70 reference statements)
2
18
0
Order By: Relevance
“…Our findings suggest the possibility of an inversely proportional relation between MVD and MGB in a limited number of breast cancer specimens. The cases in which we identified a strong MGB expression and increased MVD values, may partially support the findings of Picot et al regarding MGB-A implications in promoting cancer cell malignant features [34]. The authors of this study demonstrated that the loss of MGB-A expression determines a decrease of tumor cell proliferation [34].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings suggest the possibility of an inversely proportional relation between MVD and MGB in a limited number of breast cancer specimens. The cases in which we identified a strong MGB expression and increased MVD values, may partially support the findings of Picot et al regarding MGB-A implications in promoting cancer cell malignant features [34]. The authors of this study demonstrated that the loss of MGB-A expression determines a decrease of tumor cell proliferation [34].…”
Section: Resultssupporting
confidence: 90%
“…The cases in which we identified a strong MGB expression and increased MVD values, may partially support the findings of Picot et al regarding MGB-A implications in promoting cancer cell malignant features [34]. The authors of this study demonstrated that the loss of MGB-A expression determines a decrease of tumor cell proliferation [34]. However, these results need to be further investigated in order to become applicable in daily clinical practice.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Levels of gene expression were verified by quantitative real-time RT-PCR (RT-qPCR) as previously described [46] using specific PCR primer pairs (Supplementary Table 3). Comparative expression levels were calculated using the ΔΔCt method of Livak and Schmittgen, (2001) [47], using the hypoxanthine ribosyltransferase (HPRT) transcript as a normalizing control.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability assays. Cellular viability was monitored using the CellTiter-Blue assay (Promega, Madison, WI, USA) as previously described (29). After transfection, cells were seeded in 96 well plates (3×10 3 cells/well) where 20 μl of CellTiter-Blue substrate was added up to 100 μl/well and incubated for 1 h at 37˚C.…”
Section: Methodsmentioning
confidence: 99%